AB0333 Central Aortic Systolic Blood Pressure Measurements in Rheumatoid Arthritis: Towards the Optimization of the Blood Pressure-Associated Cardiovascular Risk Assessment. (9th June 2015) - Protogerou, A.D.; Konstantonis, G.; Aisopou, E.; Arida, A.; Zampeli, E.; Kitas, G.D.; Sfikakis, P.P.
Abstract : Background: Rheumatoid Arthritis (RA) associates with increased risk of cardiovascular disease (CVD) and high prevalence of arterial hypertension [1]. Central aortic systolic blood pressure (SBP), assessed non-invasively, is a better predictor of CVD and a better guide for anti-hypertensive treatment compared to brachial SBP [2, 3]. Data on the prevalence of central aortic SBP-based hypertension [3] are lacking in RA. Objectives: Since abnormal/uncontrolled central aortic SBP might refine CVD risk classification in RA we aimed to describe it's frequency in the presence or absence of, (i) abnormal/uncontrolled office brachial SBP, and (ii) "white coat" and masked systolic hypertension phenomena, which are frequently observed in these patients [1] Methods: Consecutive RA patients referred to out cardiovascular laboratory for CVD risk stratification underwent office brachial SBP (triplicate oscillometric recording) and central aortic SBP (with Sphygmocor device) assessments, as well as out- of-office 24-hour ambulatory, or home monitoring of brachial SBP. Results: Among 263 patients (median age 60 years IQR [52-67], women 80%), 27% and 30% had abnormal/uncontrolled brachial or central aortic measurements at office, respectively. Of all patients, 69% had both brachial and central aortic normal/controlled measurements, 25% had both brachial and central aortic abnormal/uncontrolled measurements, whereas the remaining 6% presented intermediate phenotypes (1.5% and 4.5% only brachial or only central aortic abnormal/uncontrolled measurements, respectively). Notably, abnormal central aortic measurements were noted in 100% of patients with systolic "white coat" hypertension phenomenon, as well as in 45% of patients with systolic masked hypertension phenomenon. Conclusions: Given the fact that modern technologies provide the possibility to measure simultaneously office brachial and central aortic SBP, whereas the latter guides more efficiently blood pressure management, incorporation of central aortic measurement in clinical practice might help to optimize hypertension treatment in 6% of RA patients and particularly to detect the presence of masked hypertension almost in half of them without the use of out-of-office blood pressure monitoring. References: Protogerou AD et al. Arterial hypertension assessed "out-of-office" in a contemporary cohort of rheumatoid arthritis patients free of cardiovascular disease is characterized by high prevalence, low awareness, poor control and increased vascular damage-associated "white coat" phenomenon. Arthritis Res Ther. 2013; 15(5):R142. Sharman JE, et al. Randomized trial of guiding hypertension management using central aortic blood pressure compared with best-practice care: principal findings of the BP GUIDE study. Hypertension. 2013; 62:1138-45. Cheng HM et al. Derivation and validation of diagnostic thresholds for central blood pressure measurements based on long-term cardiovascular risks. J Am Coll Cardiol. 2013; 62:1780-7. Disclosure of Interest: None declared